2011
DOI: 10.1007/s10522-011-9363-2
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet intake accelerates aging, increases expression of Hsd11b1, and promotes lipid accumulation in liver of SAMP10 mouse

Abstract: An understanding of the mechanisms of aging is important for prevention of age-related diseases. In this study, we examined age-dependent changes in lipid metabolism in the senescence-accelerated mouse (SAM)P10 fed a high-fat diet to investigate the effects of high-fat intake and aging. Tissue weights and biological parameters in plasma and liver were measured at 6 and 12 months old in SAMP10 mice fed a high-fat diet. These mice showed marked increases in liver triacylglycerol and plasma insulin levels with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 36 publications
2
33
1
Order By: Relevance
“…However, two recent studies compared HFD intake with standard chow feeding on hepatic changes in SAMP10) [23,24]. Their results showed that high-fat diet promoted lipid droplets accumulation in the livers of SAMP10 mice, contrary to normal chow feeding [23]. The same observation was confirmed by histopathological analysis of liver sections from SAMP8 mice groups in our model (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…However, two recent studies compared HFD intake with standard chow feeding on hepatic changes in SAMP10) [23,24]. Their results showed that high-fat diet promoted lipid droplets accumulation in the livers of SAMP10 mice, contrary to normal chow feeding [23]. The same observation was confirmed by histopathological analysis of liver sections from SAMP8 mice groups in our model (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…The interesting observation that may strengthen the close mechanistic relationship between aging and lipid overload are that caloric restriction potentially promotes longevity in many mammalian models, 47 whereas high-fat and/or -carbohydrate diets accelerates aging. 48 Furthermore, ischemic injury in the elderly and patients with hyperlipidemia is a major risk factor for ESRD. 49,50 In this point, therapeutic effort to restore lysosomal function and autophagic flux will pave the way to improving the clinical outcome of kidney injury related to aging or HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Reports show that health benefits of calorie restriction are mediated through the activation of sirtuins. The role of sirtuin is much relevant as HFD is known to accelerate aging and cause metabolic syndromes (Honma et al, 2012). Moreover, sirtuins are known to be effective regulators of Akt signalling and SIRT1 directly deacetylates Akt and promotes its activation (Pillai, Sundaresan, & Gupta, 2014).…”
Section: Fig 4 -Dapi and Tunel Staining To Detect Apoptosis Dapi Anmentioning
confidence: 99%